Composite targeting viscosity-reducing oil displacement system and preparation method and application thereof
Patent Information
- Application Number
- CN202611384713.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-09-08
- Publication Date
- 2026-10-13
AI Technical Summary
[0003]然而,现有的降黏驱油体系普遍存在以下技术瓶颈:其一,岩石表面吸附损耗严重;常规纳米材料降黏剂具有较高的表面能,在注入过程中极易通过静电作用或范德华力吸附于近井地带岩石表面,导致到达深部油藏的有效浓度大幅降低,实际驱油性能往往不足室内评价结果的30%,严重制约了降黏效果;其二,靶向释放能力缺失;现有降黏体系缺乏对油藏环境的智能响应能力,无法实现活性组分在目标油藏深部的定点释放,大量有效成分在非目标区域被无效消耗;其三,对复杂稠油组分分散能力不足;稠油中胶质、沥青质和蜡等重质组分结构复杂、相互作用强,单一的乳化降黏机制难以有效拆解其复杂的分子聚集体,洗油效率有限;其四,现场应用成本较高;为了弥补吸附损耗,实际使用时往往需要大幅增加注入浓度,导致药剂成本显著上升,限制了技术的规模化应用
本发明提出一种复合靶向降黏驱油体系及其制备方法与应用,通过构建功能化环糊精载体与功能化纳米材料活性组分的核-壳式复合结构,利用功能化环糊精载体的亲水外表面屏蔽效应,有效降低了功能化纳米材料活性组分的高表面能,大幅减少其在近井地带岩石表面的静电吸附损耗,使实际到达目标区域的活性浓度显著提高,解决了现有技术中纳米材料吸附损耗严重、有效利用率低的瓶颈问题;通过在功能化环糊精载体上引入pH响应基团和/或温度敏感链段,赋予复合体系对油藏环境的智能识别能力,当地层流体的pH或温度达到预设条件时,功能化环糊精载体发生构象变化或相转变,主动释放封装的功能化纳米材料活性组分,实现功能化纳米材料活性组分在目标油藏深部的定点释放,解决了现有技术中活性组分在非目标区域被无效消耗的问题;同时,复合体系的降黏效果来源于功能化纳米材料活性组分与功能化环糊精载体的双重协同机制,功能化纳米材料活性组分凭借其高表面活性和纳米尺度效应,能够高效吸附并剥离岩石表面油膜,拆解稠油中胶质、沥青质和蜡的复杂聚集体,而功能化环糊精载体的疏水空腔可包合稠油中的小分子重质组分,两者协同实现剥离、分散与降黏的一体化作用,大幅提升了洗油效率和驱油效率,解决了现有技术中单一乳化降黏机制对复杂稠油组分分散能力不足的问题;此外,由于抗吸附性能的显著提升,功能化纳米材料活性组分的有效利用率成倍增加,在现场达到同等或更优降黏效果时所需注入的药剂总量大幅降低,同时复合体系的多功能集成减少了分段注入不同药剂的作业步骤,降低了现场施工复杂度和综合成本,有效解决了现有技术中因吸附损耗导致药剂成本显著上升的问题。
Smart Images

Figure CN122898261A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of oilfield chemical enhanced oil recovery technology, specifically to a composite targeted viscosity-reducing and oil displacement system, its preparation method, and its application. Background Technology
[0002] Heavy oil resources account for a significant proportion of my country's oil reserves, but their efficient development faces enormous challenges due to their high viscosity and poor fluidity. In heavy oil blocks, such as the Liaohe Oilfield, the extremely high oil-water mobility ratio during water-drive development leads to severe water channeling along high-permeability channels, resulting in highly uneven reservoir utilization. The overall recovery rate is only about 13.5%, with a large amount of remaining oil trapped in the formation and unable to be effectively extracted, necessitating a change in development methods. Adopting viscosity-reducing flooding technology is an important direction for improving the development effect of heavy oil. After being injected into the formation, the viscosity-reducing flooding system reduces the viscosity of crude oil through contact with it, improving the oil-water mobility ratio and enhancing the oil displacement sweep efficiency and oil washing efficiency.
[0003] However, existing viscosity-reducing and oil displacement systems generally suffer from the following technical bottlenecks: First, severe adsorption loss on rock surfaces; conventional nanomaterial viscosity reducers have high surface energy and are easily adsorbed onto the near-wellbore rock surface through electrostatic interactions or van der Waals forces during injection, resulting in a significant reduction in the effective concentration reaching deep reservoirs. The actual oil displacement performance is often less than 30% of the results from laboratory evaluations, severely restricting the viscosity-reducing effect. Second, lack of targeted release capability; existing viscosity-reducing systems lack intelligent response capabilities to the reservoir environment, failing to achieve targeted release of active components at the deep part of the target reservoir, with a large amount of effective components being ineffectively consumed in non-target areas. Third, insufficient dispersion capability for complex heavy oil components; heavy components such as gums, asphaltenes, and waxes in heavy oil have complex structures and strong interactions, making it difficult for a single emulsification viscosity-reducing mechanism to effectively dismantle their complex molecular aggregates, resulting in limited oil washing efficiency. Fourth, high cost of field application; to compensate for adsorption loss, the injection concentration often needs to be significantly increased in actual use, leading to a significant increase in reagent costs and limiting the large-scale application of the technology.
[0004] Therefore, there is an urgent need to develop a novel viscosity-reducing flooding system that combines low adsorption characteristics, deep-layer targeted release capability, and high-efficiency viscosity-reducing performance to meet the technical requirements for efficient development of heavy oil reservoirs. Summary of the Invention
[0005] The purpose of this invention is to overcome the shortcomings of the prior art and provide a composite targeted viscosity-reducing oil displacement system, its preparation method and application.
[0006] To achieve the above objectives, the present invention provides the following technical solution: This application provides a composite targeted viscosity-reducing and oil displacement system, including a functionalized cyclodextrin carrier and functionalized nanomaterial active components loaded on the functionalized cyclodextrin carrier; The functionalized cyclodextrin carrier is obtained by hydrophobic modification and targeted modification of β-cyclodextrin. The targeted modification introduces targeted response groups including pH-responsive groups and / or temperature-sensitive segments. The pH-responsive group is carboxymethyl, and the temperature-sensitive segment is poly(N-isopropylacrylamide). The active components of the functionalized nanomaterials are surface-functionalized metal oxide nanoparticles and / or carbon-based nanomaterials. The metal oxide nanoparticles are Fe3O4 nanoparticles modified with an aminosilane coupling agent, and the carbon-based nanomaterials are graphene oxide grafted with long-chain hydrophobic alkylamines. The functionalized nanomaterial active components and the functionalized cyclodextrin carrier form a core-shell composite structure through amide bond chemical bonding and hydrophilic surface coating. The encapsulation refers to the formation of a core-shell composite structure by the functionalized cyclodextrin carrier through chemical bonding and spatial encapsulation between its hydrophilic outer surface and the grafted hydrophobic groups, targeting response groups, and the surface functionalized groups of the active components of the functionalized nanomaterials.
[0007] Preferably, the hydrophobic group introduced by the hydrophobic modification is a long-chain alkyl group with 8-18 carbon atoms, and the degree of substitution of the β-cyclodextrin is 1-3.
[0008] Preferably, the phase transition temperature of the poly-N-isopropylacrylamide corresponds to the reservoir temperature.
[0009] Preferably, the particle size of the metal oxide nanoparticles is 10-30 nm.
[0010] Preferably, the long-chain hydrophobic alkylamine is octadecylamine.
[0011] Preferably, the amide bond is formed by a coupling agent mediated by a coupling agent, wherein the coupling agent is EDC / NHS.
[0012] A method for preparing the composite targeted viscosity-reducing and oil displacement system as described above includes the following steps: β-cyclodextrin was hydrophobically modified to obtain hydrophobically modified cyclodextrin. The hydrophobically modified cyclodextrin was subjected to targeted modification to obtain a functionalized cyclodextrin carrier. Surface functionalization modification of nanomaterials yields functionalized active components of nanomaterials; The functionalized nanomaterial active components are combined with the functionalized cyclodextrin carrier to obtain the composite targeted viscosity-reducing and oil displacement system.
[0013] Preferably, the targeted modification treatment involves introducing carboxymethyl groups via a chloroacetic acid grafting reaction, or grafting poly-N-isopropylacrylamide via an atom transfer radical polymerization reaction. The surface functionalization modification is achieved by treating Fe3O4 nanoparticles with an aminosilane coupling agent to introduce amino groups, or by grafting graphene oxide with octadecylamine.
[0014] Application of a composite targeted viscosity reduction and oil displacement system in heavy oil reservoir development.
[0015] Preferably, the application is to inject the composite targeted viscosity-reducing and oil displacement system into the reservoir; the composite targeted viscosity-reducing and oil displacement system is configured to release the active components of the functionalized nanomaterials in response to changes in pH and / or temperature of the reservoir environment.
[0016] Compared with the prior art, this application has the following beneficial effects: This invention proposes a composite targeted viscosity-reducing and oil displacement system, its preparation method, and its application. By constructing a core-shell composite structure of a functionalized cyclodextrin carrier and functionalized nanomaterial active components, and utilizing the hydrophilic outer surface shielding effect of the functionalized cyclodextrin carrier, the high surface energy of the functionalized nanomaterial active components is effectively reduced, significantly decreasing electrostatic adsorption loss on the rock surface near the wellbore. This results in a significant increase in the actual active concentration reaching the target area, solving the bottleneck problems of severe adsorption loss and low effective utilization rate of nanomaterials in existing technologies. Furthermore, by introducing pH-responsive groups and / or temperature-sensitive segments onto the functionalized cyclodextrin carrier, the composite system is endowed with intelligent recognition capabilities of the reservoir environment. When the pH or temperature of the formation fluid reaches preset conditions, the functionalized cyclodextrin carrier undergoes a conformational change or phase transition, actively releasing the encapsulated functionalized nanomaterial active components. This achieves targeted release of the functionalized nanomaterial active components deep within the target reservoir, solving the problem of ineffective consumption of active components in non-target areas in existing technologies. Simultaneously, the composite… The viscosity-reducing effect of the system stems from the dual synergistic mechanism of the functionalized nanomaterial active components and the functionalized cyclodextrin carrier. The functionalized nanomaterial active components, with their high surface activity and nanoscale effect, can efficiently adsorb and strip oil films from rock surfaces, breaking down complex aggregates of gums, asphaltenes, and waxes in heavy oil. Meanwhile, the hydrophobic cavities of the functionalized cyclodextrin carrier can encapsulate small-molecule heavy components in heavy oil. The two work synergistically to achieve an integrated effect of stripping, dispersion, and viscosity reduction, significantly improving oil washing and displacement efficiency. This solves the problem of insufficient dispersion of complex heavy oil components by a single emulsification viscosity-reducing mechanism in existing technologies. Furthermore, due to the significantly improved anti-adsorption performance, the effective utilization rate of the functionalized nanomaterial active components increases exponentially, drastically reducing the total amount of reagent required to achieve the same or better viscosity-reducing effect on-site. Simultaneously, the multifunctional integration of the composite system reduces the steps of injecting different reagents in stages, lowering on-site construction complexity and overall cost, effectively solving the problem of significantly increased reagent costs due to adsorption loss in existing technologies. Attached Figure Description
[0017] Figure 1 This is a graph showing the trend of viscosity reduction rate as a function of the concentration of the composite targeted viscosity reduction and oil displacement system. Figure 2 Microscopic emulsion state diagrams of emulsions prepared under different concentration conditions for the composite targeted viscosity-reducing and oil displacement system; Figure 3 This is a graph showing the trend of emulsion particle size as a function of the concentration of the composite targeted viscosity-reducing and oil displacement system. Figure 4 The viscosity reduction characteristics are shown in the graphs under different temperature conditions. Figure 5 The diagram shows the microscopic emulsification state of the mixture under different temperature conditions; Figure 6 This is a graph showing the trend of viscosity reduction rate as a function of aqueous phase pH. Figure 7 Microscopic emulsification state diagrams of emulsions prepared under different pH conditions. Detailed Implementation
[0018] The present invention will be further described in detail below with reference to the embodiments and accompanying drawings, but the implementation of the present invention is not limited thereto; the experimental methods in the following embodiments without specific conditions are generally performed under conventional conditions or under the conditions recommended by the manufacturer; unless otherwise stated, all parts are parts by weight and all percentages are weight percentages; the materials, reagents, etc. used in the following embodiments are commercially available unless otherwise specified.
[0019] Example 1 This embodiment provides a method for preparing a pH-responsive functionalized cyclodextrin carrier, the specific steps of which are as follows: Hydrophobic modification: 10g of β-cyclodextrin was dissolved in 100mL of deionized water, 2.5g of NaOH was added, the temperature was raised to 70℃, and 3.5g of dodecyl bromide was slowly added dropwise. The mixture was stirred at a constant temperature for 8 hours. After cooling, the mixture was neutralized with hydrochloric acid, precipitated with acetone, filtered, and dried to obtain hydrophobically modified dodecyl-β-cyclodextrin with a degree of substitution (DS) of about 2. The introduced hydrophobic group is dodecyl, which is a long-chain alkyl group with 8-18 carbon atoms.
[0020] pH-responsive functionalization modification: 5g of the above dodecyl-β-cyclodextrin was dissolved in 50mL of isopropanol, 1.5g of NaOH was added, and 2g of chloroacetic acid was slowly added while stirring. The reaction was carried out at 60℃ for 5 hours. After cooling, the mixture was neutralized, purified by dialysis, and freeze-dried to obtain a functionalized cyclodextrin carrier with both hydrophobic groups and carboxymethyl groups (pH-responsive groups), denoted as CM-C. 12 -β-CD.
[0021] Example 2 5g of the dodecyl-β-cyclodextrin prepared in Example 1 was dissolved in an appropriate amount of solvent, and N-isopropylacrylamide polymerization was initiated on its surface by atom transfer radical polymerization. Using 2-bromoisobutyryl bromide as the initiator and CuBr / PMDETA as the catalytic system, the molar ratio of NIPAM monomer to initiator was controlled so that the phase transition temperature of the obtained PNIPAM segments was about 65°C. After the reaction, the precipitate was washed and dried to obtain a temperature-sensitive functionalized cyclodextrin carrier. This carrier achieves the encapsulation and release of the active components of functionalized nanomaterials through the conformational change of temperature-sensitive segments.
[0022] Example 3 2.78g FeSO4·7H2O and 5.40g FeC l3 • 6H2O was dissolved in 100mL of deionized water, heated to 80℃ under nitrogen protection, and 15mL of NH4OH (25%) was rapidly added with vigorous stirring. The reaction was carried out for 30 minutes. The precipitate was separated by an external magnetic field, washed with water until neutral, and dispersed in an ethanol / water mixture. 2mL of aminosilane coupling agent APTES was added, and the reaction was carried out at 70℃ for 4 hours. After magnetic separation, washing, and drying, aminated Fe3O4 nanoparticles with a particle size of about 20nm were obtained. Amino groups were introduced onto the surface of the active component of this functionalized nanomaterial.
[0023] Example 4 Graphene oxide was prepared using the Hummers method. Graphite powder was mixed with concentrated sulfuric acid and sodium nitrate, and potassium permanganate was slowly added under ice bath conditions. After heating and reacting, hydrogen peroxide was added to terminate the reaction. After centrifugation, washing, ultrasonic exfoliation, and drying, graphene oxide (GO) was obtained. The GO was then modified by hydrophobic grafting: GO was dispersed in an appropriate amount of solvent, and EDC / NHS was added to activate the carboxylic acid groups on the surface of GO. Octadecylamine was then added, and the reaction was stirred at room temperature for 12 hours. After centrifugation, washing, and drying, long-chain hydrophobic alkylamine-grafted functionalized graphene oxide (GO-octadecylamine) was obtained.
[0024] Example 5 2g of CM-C prepared in Example 1 12 -β-CD was dissolved in 50 mL of phosphate buffer (pH=6.0), and 0.4 g of EDC and 0.24 g of NHS were added to activate the carboxyl group for 30 minutes. Then, 1 g of the aminated Fe3O4 nanoparticle suspension prepared in Example 3 was added, and the mixture was ultrasonically dispersed for 30 minutes and stirred at room temperature for 12 hours. The reaction product was purified by dialysis using a dialysis bag (molecular weight cutoff 10000 Da) for 48 hours and then freeze-dried to obtain amide-linked CM-C. 12 -β-CD@Fe3O4 composite targeted viscosity reduction and oil displacement system.
[0025] Example 6 The functionalized cyclodextrin carrier was dissolved in deionized water, and Fe was added. 2+ and Fe 3+ Mixed solution (FeSO4·7H2O and FeC) l3 ·6H2O was prepared at a molar ratio of 1:2. NH4OH solution was added dropwise under stirring to generate Fe3O4 nanoparticles in situ within the functionalized cyclodextrin system. These nanoparticles formed a core-shell composite structure through chemical bonding and hydrophilic surface coating. After centrifugation, washing, and freeze-drying, Fe3O4@β-CD composite powder was obtained.
[0026] Example 7 The GO-octadecylamine prepared in Example 4 and the thermosensitive functionalized cyclodextrin carrier prepared in Example 2 were chemically bonded together. The GO-octadecylamine was dispersed in an appropriate amount of solvent, the thermosensitive functionalized cyclodextrin carrier was added, and the mixture was ultrasonically dispersed for 30 minutes. The mixture was stirred at room temperature for 12 hours. After dialysis purification and freeze drying, a composite targeted viscosity-reducing and oil-displacing system containing the GO-octadecylamine active component was obtained.
[0027] Example 8 Equal amounts of the functionalized nanomaterial active component of the present invention's composite system (Example 5) and bare Fe3O4 nanoparticles were injected into a sand-filled tube model, and the concentration at the outlet end was measured. The results showed that the penetration rate of bare Fe3O4 nanoparticles was only 28%, while the penetration rate of the composite system of the present invention was as high as 85%, improving the anti-adsorption performance by more than 3 times. The shielding effect of the hydrophilic outer surface of the functionalized cyclodextrin carrier effectively reduced the high surface energy of Fe3O4 nanoparticles, reduced the electrostatic adsorption between nanoparticles and rock surfaces, and broke through the technical bottleneck of easy adsorption in near-wellbore areas.
[0028] It should be noted that the coating described in this application refers to the formation of a core-shell composite structure by the functionalized cyclodextrin carrier through chemical bonding and spatial encapsulation between the hydrophilic outer surface and the grafted hydrophobic groups, the targeted responsive groups and the functionalized groups on the surface of the nanoparticles, rather than the physical entry of the nanoparticles into the molecular cavity of β-cyclodextrin.
[0029] Example 9 It should be noted that: viscosity reduction rate = (crude oil viscosity - mixture viscosity) / crude oil viscosity × 100%, where the crude oil viscosity is the crude oil viscosity value without the addition of the composite system at the same temperature, measured by a rotational viscometer; the mixture viscosity is the viscosity value of the oil-water mixture after stirring at the same temperature.
[0030] Composite targeted viscosity-reducing and oil displacement systems with different mass concentrations were prepared using simulated formation water with a salinity of 9982 mg / L and a pH of approximately 7.5. The concentrations were 0.05%, 0.1%, 0.3%, 0.5%, 0.8%, and 1.0%, respectively. Liaohe heavy oil was used as the experimental oil sample (viscosity approximately 8500 mPa·s at 50℃ and approximately 2586 mPa·s at 70℃) for evaluation. The experimental conditions were: experimental temperature 70℃, oil-water ratio 5:5, stirring speed 3000 rpm, and stirring time 3 min.
[0031] like Figure 1 As shown, attached Figure 1 The graph shows the trend of viscosity reduction rate as a function of the concentration of the composite targeted viscosity reduction and oil displacement system; the horizontal axis represents the concentration of the composite targeted viscosity reduction and oil displacement system (%), the left vertical axis represents viscosity (mPa·s), and the right vertical axis represents viscosity reduction rate (%). Figure 1 It can be seen that: at a concentration of 0.05%, the viscosity is 378 mPa·s, and the viscosity reduction rate is 85.38%; at a concentration of 0.1%, the viscosity is 127.3 mPa·s, and the viscosity reduction rate is 95.08%; at a concentration of 0.3%, the viscosity is 45.37 mPa·s, and the viscosity reduction rate is 98.25%; at a concentration of 0.5%, the viscosity is 28.62 mPa·s, and the viscosity reduction rate is 98.89%; at a concentration of 0.8%, the viscosity is 20.39 mPa·s, and the viscosity reduction rate is 99.21%; at a concentration of 1.0%, the viscosity is 18.75 mPa·s, and the viscosity reduction rate is 99.27%. The viscosity reduction rate increases with increasing concentration and tends to stabilize after the concentration reaches 0.5%.
[0032] like Figure 2 As shown, attached Figure 2 The microemulsion states of the emulsions prepared under different concentration conditions of the composite targeted viscosity-reducing and oil displacement system are shown in the figure. The figures are labeled with microemulsion photographs at six concentrations: 0.05%, 0.1%, 0.3%, 0.5%, 0.8%, and 1.0%, with a scale bar of 50 μm. Figure 2 It can be seen that as the concentration increases, the size of the emulsion droplets gradually decreases and the distribution becomes more uniform. At a concentration of 0.5% and above, a fine and dense emulsion is formed.
[0033] like Figure 3 As shown, attached Figure 3 The figure shows the trend of emulsion particle size variation with the concentration of the composite targeted viscosity-reducing and oil displacement system; the horizontal axis represents the concentration of the composite targeted viscosity-reducing and oil displacement system (%), and the vertical axis represents the average particle size of the emulsion (μm). Figure 3It can be seen that: at a concentration of 0.05%, the average particle size of the emulsion is 50.72 μm; at a concentration of 0.1%, the average particle size is 24.14 μm; at a concentration of 0.3%, the average particle size is 16.51 μm; at a concentration of 0.5%, the average particle size is 10.43 μm; at a concentration of 0.8%, the average particle size is 8.86 μm; and at a concentration of 1.0%, the average particle size is 7.97 μm. The average particle size of the emulsion decreases significantly with increasing concentration, indicating that the composite targeted viscosity-reducing and oil-displacing system has excellent emulsifying and viscosity-reducing properties for heavy oil, and still has strong emulsifying ability even under ultra-low concentration conditions.
[0034] Example 10 A composite targeted viscosity-reducing and oil displacement system with a mass concentration of 0.5% was prepared using simulated formation water; the Liaohe heavy oil was used as the experimental oil sample for evaluation.
[0035] It should be noted that: viscosity reduction rate = (crude oil viscosity - mixture viscosity) / crude oil viscosity × 100%, where the crude oil viscosity is the crude oil viscosity value without the addition of the composite system at the same temperature, measured by a rotational viscometer; the mixture viscosity is the viscosity value of the oil-water mixture after stirring at the same temperature.
[0036] The experimental conditions were: oil-water ratio 5:5, stirring speed 3000 rpm, stirring time 3 min; first, the mixture was prepared at 50℃, and the viscosity reduction rate and microemulsion state were tested; then the temperature was raised to 70℃, and the mixture was stirred again for 3 min, and the viscosity reduction rate and microemulsion state of the mixture were tested.
[0037] like Figure 4 As shown, attached Figure 4 The graph shows the viscosity reduction characteristics under different temperature conditions; the horizontal axis represents temperature, the left vertical axis represents viscosity (mPa·s), and the right vertical axis represents viscosity reduction rate (%). Figure 4 It can be seen that at a temperature of 50℃, the viscosity is 8456 mPa·s, and the viscosity reduction rate is 0.52%. It should be noted that the viscosity of the mixture at 50℃ (8456 mPa·s) is slightly lower than that of crude oil (8500 mPa·s), and the viscosity reduction rate is only 0.52%. This is because although the composite system does not undergo targeted release at low temperatures, the surface functionalized nanomaterial active components in the system still have extremely weak interfacial activity. Moreover, the viscosity of the W / O type emulsion formed after oil-water mixing is close to that of pure oil, so the viscosity reduction rate is extremely low, but not zero. This result is consistent with the data of crude oil viscosity of approximately 8500 mPa·s at 50℃ in Example 9.
[0038] At 70℃, the viscosity is 29.03 mPa·s, and the viscosity reduction rate is 98.88%. When the temperature is below the phase transition temperature (the system does not respond at 50℃, i.e., below the phase transition temperature), the nanoparticles coated on the hydrophilic surface of the functionalized cyclodextrin carrier cannot be released, the system has no interfacial interaction ability, and the viscosity reduction rate is extremely low. When the temperature is raised above the phase transition temperature (70℃), the active components of the functionalized nanomaterials are rapidly released by the nanoparticles coated on the hydrophilic surface of the functionalized cyclodextrin carrier, the system has strong interfacial interaction ability, and the viscosity reduction rate is greatly improved.
[0039] like Figure 5 As shown, attached Figure 5 This figure shows the microscopic emulsification state of the mixture under different temperature conditions; the left and right photos are labeled 50℃ and 70℃ respectively, and the scale bar is 50μm for both. Figure 5 It can be seen that at a temperature of 50℃, there are only a few dispersed particles in the mixture and no emulsification is observed; at a temperature of 70℃, a large number of fine and dense emulsion droplets are formed in the mixture, and the emulsification state is excellent; this confirms the temperature-targeted release characteristics of the composite targeted viscosity reduction and oil displacement system.
[0040] Example 11 The pH of simulated formation water with a salinity of 9982 mg / L and a pH of approximately 7.5 was adjusted to 2, 4, 6, and 7.5 using HCl. Composite targeted viscosity-reducing and oil displacement systems with a mass concentration of 0.5% were prepared using aqueous phases with different pH values. Liaohe heavy oil was used as the experimental oil sample for evaluation.
[0041] The experimental conditions were: temperature 70℃, oil-water ratio 5:5, stirring speed 3000rpm, and stirring time 3min.
[0042] like Figure 6 As shown, attached Figure 6 The graph shows the viscosity reduction rate as a function of aqueous pH; the horizontal axis represents pH, the left vertical axis represents viscosity (mPa·s), and the right vertical axis represents viscosity reduction rate (%). Figure 6 It can be seen that: at pH=2, the viscosity is 2517 mPa·s, and the viscosity reduction rate is 2.67%; at pH=4, the viscosity is 2498 mPa·s, and the viscosity reduction rate is 3.40%; at pH=6, the viscosity is 434 mPa·s, and the viscosity reduction rate is 83.22%; at pH=7.5, the viscosity is 28.75 mPa·s, and the viscosity reduction rate is 98.89%. When the pH of the aqueous phase is low (pH=2 and pH=4), the nanoparticles coated with the hydrophilic surface of the functionalized cyclodextrin carrier cannot be released, the system has no interfacial interaction ability, and the viscosity reduction rate is extremely low; when pH=6, the nanoparticles coated with the hydrophilic surface of the functionalized cyclodextrin carrier begin to be released, and the interfacial interaction ability of the system gradually increases; when pH=7.5, the nanoparticles are fully released, and the viscosity reduction rate reaches its highest level.
[0043] like Figure 7 As shown, attached Figure 7 The images show the microscopic emulsification states of emulsions prepared under different pH conditions; the four photographs are labeled as pH=2, pH=4, pH=6, and pH=7.5, respectively, with a scale bar of 50 μm. Figure 7 It can be seen that no emulsification was observed in the mixture under pH=2 and pH=4 conditions; emulsion droplets began to appear in the mixture under pH=6 conditions; and a large number of fine and dense emulsion droplets were formed in the mixture under pH=7.5 conditions, indicating excellent emulsification. This confirms the pH-targeted release characteristics of the composite targeted viscosity reduction and oil displacement system.
[0044] Example 12 Using Liaohe heavy oil with a viscosity of approximately 8500 mPa·s at 50℃ as the experimental oil sample, a dual-parallel core displacement experiment was conducted.
[0045] The experimental procedure was as follows: first, water flooding was carried out to a water cut of 98%, then a 0.3% concentration of composite targeted viscosity-reducing oil displacement system solution was injected, and then water flooding was carried out again to a water cut of 98%.
[0046] The results show that after displacement using the composite targeted viscosity-reducing oil displacement system of the present invention, the recovery rate of low-permeability cores increased by 22.6% on the basis of waterflooding, and the total recovery rate was significantly better than that of conventional viscosity reducers, increasing by 8.3%. This proves that the composite system of the present invention can effectively utilize the remaining oil in low-permeability layers and improve the overall recovery rate.
[0047] Example 13 The temperature-sensitive composite system containing GO-octadecylamine active component prepared in Example 7 was tested for viscosity reduction at 50°C and 70°C. The results showed that the viscosity reduction was extremely low at 50°C and reached more than 96% at 70°C, exhibiting obvious temperature-targeted release characteristics.
[0048] CM-C prepared using Example 5 12 The viscosity reduction rate of the -β-CD@Fe3O4 composite system was tested under different pH conditions. The results showed that the viscosity reduction rate was extremely low at pH=4, while it reached more than 98% at pH=7.5. This composite system has obvious pH-targeted release characteristics.
[0049] The above results verify that both implementation methods of the targeted responsive groups in this invention can achieve intelligent release of active components of functionalized nanomaterials.
[0050] It will be apparent to those skilled in the art that the present invention is not limited to the details of the exemplary embodiments described above, and that the invention can be implemented in other specific forms without departing from its spirit or essential characteristics. Therefore, the embodiments should be considered in all respects as exemplary and non-limiting, and the scope of the invention is defined by the appended claims rather than the foregoing description. Thus, all variations falling within the meaning and scope of equivalents of the claims are intended to be included within the present invention. No reference numerals in the claims should be construed as limiting the scope of the claims.
[0051] Furthermore, it should be understood that although this specification describes embodiments, not every embodiment contains only one independent technical solution. This narrative style is merely for clarity. Those skilled in the art should consider the specification as a whole, and the technical solutions in each embodiment can also be appropriately combined to form other embodiments that can be understood by those skilled in the art.
Claims
1. A composite targeted viscosity-reducing oil displacement system, characterized in that, It includes a functionalized cyclodextrin carrier and a functionalized nanomaterial active component loaded on the functionalized cyclodextrin carrier; The functionalized cyclodextrin carrier is obtained by hydrophobic modification and targeted modification of β-cyclodextrin. The targeted modification introduces targeted response groups including pH-responsive groups and / or temperature-sensitive segments. The pH-responsive group is carboxymethyl, and the temperature-sensitive segment is poly(N-isopropylacrylamide). The active components of the functionalized nanomaterials are surface-functionalized metal oxide nanoparticles and / or carbon-based nanomaterials. The metal oxide nanoparticles are Fe3O4 nanoparticles modified with an aminosilane coupling agent, and the carbon-based nanomaterials are graphene oxide grafted with long-chain hydrophobic alkylamines. The functionalized nanomaterial active components and the functionalized cyclodextrin carrier form a core-shell composite structure through amide bond chemical bonding and hydrophilic surface coating. The encapsulation refers to the formation of a core-shell composite structure by the functionalized cyclodextrin carrier through chemical bonding and spatial encapsulation between its hydrophilic outer surface and the grafted hydrophobic groups, targeting response groups, and the surface functionalized groups of the active components of the functionalized nanomaterials.
2. The composite targeted viscosity-reducing and oil displacement system according to claim 1, characterized in that, The hydrophobic groups introduced by the hydrophobic modification are long-chain alkyl groups with 8-18 carbon atoms, and the degree of substitution of β-cyclodextrin is 1-3.
3. The composite targeted viscosity-reducing and oil displacement system according to claim 1, characterized in that, The phase transition temperature of the poly-N-isopropylacrylamide corresponds to the reservoir temperature.
4. The composite targeted viscosity-reducing and oil displacement system according to claim 1, characterized in that, The particle size of the metal oxide nanoparticles is 10-30 nm.
5. The composite targeted viscosity-reducing and oil displacement system according to claim 1, characterized in that, The long-chain hydrophobic alkylamine is octadecylamine.
6. The composite targeted viscosity-reducing and oil displacement system according to claim 1, characterized in that, The amide bond is formed by a coupling agent mediated by an EDC / NHS.
7. A method for preparing a composite targeted viscosity-reducing and oil displacement system as described in any one of claims 1 to 6, characterized in that, Includes the following steps: β-cyclodextrin was hydrophobically modified to obtain hydrophobically modified cyclodextrin. The hydrophobically modified cyclodextrin was subjected to targeted modification to obtain a functionalized cyclodextrin carrier. Surface functionalization modification of nanomaterials yields functionalized active components of nanomaterials; The functionalized nanomaterial active components are combined with the functionalized cyclodextrin carrier to obtain the composite targeted viscosity-reducing and oil displacement system.
8. The preparation method according to claim 7, characterized in that, The targeted modification treatment involves introducing carboxymethyl groups via chloroacetic acid grafting or grafting poly-N-isopropylacrylamide via atom transfer radical polymerization. The surface functionalization modification involves treating Fe3O4 nanoparticles with an aminosilane coupling agent to introduce amino groups, or grafting graphene oxide with octadecylamine.
9. The application of the composite targeted viscosity-reducing and oil displacement system according to any one of claims 1 to 6 in the development of heavy oil reservoirs.
10. The application according to claim 9, characterized in that, The application is to inject the composite targeted viscosity-reducing and oil displacement system into the reservoir; the composite targeted viscosity-reducing and oil displacement system is configured to release the active components of the functionalized nanomaterials in response to changes in pH and / or temperature of the reservoir environment.